A representation of partial spatial knowledge: a cognitive map approach for evacuation simulations - Andresen, Erik; Chraibi, Mohcine; Seyfried, Armin (Transportmetrica (Abingdon, Oxfordshire, UK), 2018)
Usually, routing models in evacuation simulations assume that agents have comprehensive and global knowledge about the building's structure. They neglect the fact that pedestrians might possess no or only parts of information about their position relative to final exits and possible routes leading to them. For the sake of a more realistic description of the routing process, we introduce the systematics of using partial spatial knowledge. Particularly, we present an agent-based approach modeling the inaccurate mental representation of pedestrians' spatial knowledge (the cognitive map). In addition, the model considers further principles and constraints of human wayfinding. Furthermore, we present results of a field study which we conducted in an office building. The purpose of this study was to investigate route choices of people in dependency on their familiarity with the building. Our modeling approach is then calibrated using the obtained results. In this context, the distribution of routes which were used by the subjects are compared with results of the model.